Identifying core leadership competencies to success non-communicable disease control and prevention programs: A mixed-methods study - Jafar Sadegh Tabrizi; Yegane Partovi; Andrew Wilson; Kamal Gholipour; Mostafa Farahbakhsh; Tohid Jafari Koshki; Ahmad Koosha; Jabreil Sharbafi (PLoS ONE, 2025)
Introduction Strengthening strong leadership skills is essential for program managers to successfully implement programs for the prevention and control of noncommunicable diseases (NCDs). This study identified leadership competencies for managers of individuals with noncommunicable diseases in Iran. Methods The study had three steps: a literature review, an expert panel, and a Delphi technique survey. First, the literature was reviewed to compile a list of leadership competencies in the field of primary health care (public health, NCDs). To refine and adapt the original list of leadership competencies, it was provided to the expert panel in two stages. The list of leadership competencies was sent via email to 30 experts over the course of two Delphi rounds. Descriptive statistics were used to analyze the outcomes. Results Fifteen leadership competencies, comprising multisectoral collaboration, political awareness, evidence-informed decision making, risk and disaster management, planning, innovation, leading and managing change, team building, communication, quality improvement, systematic thinking, management, ethics and professionalism, motivation and inspiration and personality, were identified. Conclusion The leadership competencies identified in this study can be a helpful tool in evaluating and identifying skills, knowledge, and attitudes with program managers for the prevention and control of NCDs and in designing training programs to strengthen leadership skills.